1995
DOI: 10.1523/jneurosci.15-01-00798.1995
|View full text |Cite
|
Sign up to set email alerts
|

Representation of curved surfaces in responses of mechanoreceptive afferent fibers innervating the monkey's fingerpad

Abstract: The aim was to elucidate how the population of digital nerve afferents signals information about the shape of objects in contact with the fingerpads during fine manipulations. Responses were recorded from single mechanoreceptive afferent fibers in median nerves of anesthetized monkeys. Seven spherical surfaces were used, varying from a highly curved surface (radius, 1.44 mm; curvature, 694 m-1) to a flat surface (radius, infinity; curvature, 0 m-1). These were applied to the fibers' receptive fields, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 30 publications
11
82
0
1
Order By: Relevance
“…These afferents offer many types of information that may be of relevance for the control of fingertip forces in manipulation, for instance, information related to frictional slips and creep Srinivasan et al, 1990;Milner et al, 1991), the shape of the contact surface (Goodwin et al, 1995), and contact angle (Goodwin and Morley, 1987), as well as distribution within the contact area of normal and tangential forces Srinivasan et al, 1990;. Thus, information related to object shape in the present study should have been readily available from signals in populations of tactile afferents.…”
Section: Somatosensory Afferent Sourcesmentioning
confidence: 98%
“…These afferents offer many types of information that may be of relevance for the control of fingertip forces in manipulation, for instance, information related to frictional slips and creep Srinivasan et al, 1990;Milner et al, 1991), the shape of the contact surface (Goodwin et al, 1995), and contact angle (Goodwin and Morley, 1987), as well as distribution within the contact area of normal and tangential forces Srinivasan et al, 1990;. Thus, information related to object shape in the present study should have been readily available from signals in populations of tactile afferents.…”
Section: Somatosensory Afferent Sourcesmentioning
confidence: 98%
“…Goodwin et al stimulated the human finger pad with rigid spherical stimuli of varying radii, and showed that slight changes in curvature (especially for stimuli smaller than a single finger pad) can drastically effect the firing rate of SA I mechanoreceptors [12,14] and the perception [13] of the stimulus curvature. Similarly, Lamotte et al showed that peak pressures vary inversely with the object radius, such that stronger responses would be evoked from the smaller lumps (larger curvature) [21].…”
Section: Softness Discriminationmentioning
confidence: 99%
“…When scanning a texture with a probe, the perception of the contour of the probe, which is in direct contact with the fingers, is likely mediated peripherally by SA1 afferents (Goodwin et al 1995;LaMotte et al 1998). The roughness of the scanned surface, however, seems to be a function of the vibrations elicited in the probe as it is scanned across the surface (see Figure 6, left panel and Figure 11A).…”
Section: Neural Mechanisms Of Texture Perceptionmentioning
confidence: 99%